Uso de problemas relacionados à urbanização para contextualização no ensino de física - Rizo, Marcio José de Souza (2022)
Many students and even teachers show difficulties in contextualizing Physics content in their daily practices. To collaborate in this task several approaches can be used, among them Teaching-Learning Sequences (TLS), tools used in teaching with the goal of achieving meaningful learning, where lesson plans, in modules covering single topics, are sequential and concatenated. In this context, this work aimed to evaluate, in terms of learning Physics concepts, an educational product, a didactic guide for the teacher, composed of three distinct TLS, developed with themes that involve Urbanism and its consequences for quality of life: the issue of traffic light synchronization, for the 1st year of High School, heat islands, for the 2nd year, and noise pollution, for the 3rd year. The product was applied in a public school in the city of Pontes e Lacerda, in Mato Grosso. In a qualitative approach, the research methodology used participant observation, whose analysis was based on the written and oral arguments produced by the students. The teaching sequences presented satisfactory results, where many students showed signs of significant learning, besides feeling motivated and interested in the subjects, mainly by the application of the content in their daily lives and the use of information technology in the classes. The Product proved to be suitable for use in the classroom, and can be easily adapted by the teacher to their reality.